ENHANCEMENT OF PRODUCTIVITY BY OVERALL EQUIPMENT EFFECTIVENESS PERFORMANCE TIME REDUCTION IN FOOD INDUSTRIES - Abdul Rasib, Amir Hamzah; Abdullah, Rohana; Wakhi Anuar, Nur Farah Bazilah; Mohamad Rafaai, Z. F.; Noor, R.M.; Mansoor, H.O. (Penerbit Universiti Teknikal Malaysia Melaka, 2022)
Productivity is an important factor in the manufacturing industry is productivity. Nowadays, the critical issue in current operation at most industries is a low productivity because of uncertain poor performance in operation such as performance of quality and operation stop or delay without any notices due to lack performance of machines or equipment. Therefore, the objective of this paper is to identify the root causes which effect to poor performance of quality and operation by applying Overall Equipment Effectiveness (OEE). Ultimately, propose appropriate action to be taken by the respective company to increase the productivity and output in production line. To cater appropriate performance measures, this study used a descriptive quantitative method with an Overall Equipment Effectiveness (OEE) as measuring tool based on Performance, Availability and Quality percentage. Based on the results found that Performance with 71.6% is the main contribution to the low productivity. Therefore, to identify a root cause of the poor performance as one of OEE’s components by using the Ishikawa diagram, as well as to make any suggestions for improvement using the Whywhy analysis. Thus, according to the results of OEE’s factors (Performance, Availability, and Quality) at the current level were determined the causes for improvement proposed based on six big losses. Finally, the results of OEE able as a measurement reference to propose suggestion for improvement.